Zakat Distribution Research: A Bibliometric Analysis Using VOSViewer for the 2015–2024 Period - Farah Syadza Salsabila; Windi Windi (Indonesian Journal Publisher, 2025)
Economic inequality in Indonesia remains high, and personal poverty continues due to uneven income distribution. Zakat, as part of Islamic economic philanthropy, plays an important role in alleviating poverty by redistributing wealth. This study employs a bibliometric analysis using data from the Dimensions AI database, focusing on the keywords